The prominent hypointense vessel sign on susceptibility-weighted imaging (SWI) as a potential imaging biomarker for poor clinical outcome in acute ischemic stroke (AIS) - Abdul Rashid, Anna Misyail; Mohd Yaakob, Mohd Naim; Kamis, Mohd Fandi Al-Khafiz; Md Noh, Mohamad Syafeeq Faeez (Elsevier, 2022)
Susceptibility-weighted imaging (SWI) is a relatively new magnetic resonance imaging (MRI) technique used in the workup and diagnosis of brain pathologies. In the context of acute ischemic stroke (AIS), it is increasingly becoming useful in the diagnosis, treatment, and further management of these patients. An elderly man with metabolic syndrome presented to us with an acute onset of right sided body weakness and aphasia. Urgent imaging via MRI noted a left middle cerebral artery (MCA) occlusion. Diffusion-weighted imaging (DWI)/fluid attenuated inversion recovery (FLAIR) mismatch was noted with an acute infarct involving the left MCA territory; hence, treatment with intravenous (IV) thrombolysis was administered. On SWI, the prominent hypointense vessel sign was noted. Recanalization of the occluded left MCA was seen on diagnostic cerebral angiography post IV thrombolysis, however, the patient was noted to have early neurological deterioration (END) and poor early stage clinical outcome, despite repeat MRI showing recanalization of the left MCA occlusion and reversal of the prominent hypointense vessel sign on SWI. Presence of the prominent hypointense vessel sign on SWI in AIS patients is associated with poor clinical outcome, unsuccessful recanalization rates, END, poor early stage clinical outcome, and infarct core progression. Some studies have shown an association between this imaging sign and poor collateral circulation status. Therefore, this imaging sign could potentially prove to be a useful imaging biomarker. However, more studies are needed to validate this theory.